Oxysophocarpine suppresses hepatocellular carcinoma growth and sensitizes the therapeutic blockade of anti‐Lag‐3 via reducing FGL1 expression. (18th August 2020) - Wang, Jianchu; Wei, Wang; Tang, Qianli; Lu, Libai; Luo, Zongjiang; Li, Wenchuan; Lu, Yuan; Pu, Jian
Abstract: Hepatocellular carcinoma (HCC) is an aggressive malignancy with limited effective treatments and ranks as the second most lethal tumor. Immunotherapy has brought great hope for HCC treatment. Oxysophocarpine is a bioactive alkaloid which poses various pharmacological functions including neuroprotective, anti‐virus, anti‐convulsant, and anti‐nociception. However, there is little systematic study of Oxysophocarpine against HCC and its underlying potential and mechanism combined with immunotherapy in HCC treatment remain poorly unknown. This study was aimed to investigate whether Oxysophocarpine can distinctly suppress HCC cells and sensitize the immunotherapy of CD8 + T cells against HCC. We used HepG2, Hepa1‐6, and primary CD8 + T cells to perform in vitro assays and Hepa1‐6 subcutaneous tumor to conduct in vivo assay. Oxysophocarpine inhibited the proliferation and increased the apoptosis of HepG2 and Hepa1‐6 cells, meanwhile suppressed the migration of HepG2 and Hepa1‐6 cells. Oxysophocarpine sensitized the Lag‐3 immunotherapy effect of CD8 + T cells against HCC in vivo and in vitro by decreasing Fibrinogen‐like protein 1 (FGL1) expression through downregulating IL‐6‐mediated JAK2/STAT3 signaling, whereas Oxysophocarpine treatment had a little effect of CD8 + T cells cytotoxicity function against HCC with PD‐1, Tim‐3, or TIGIT blockade. Our studies provided preclinical basis for clinical application of Oxysophocarpine. Abstract : Oxysophocarpine inhibited the proliferation, migration, and increased the apoptosis of HCC cells. Oxysophocarpine sensitized the Lag‐3 immunotherapy effect of CD8 +  T against HCC by decreasing FGL1 expression through IL‐6‐mediated JAK2/STAT3 pathway.